Psychometric Properties of the Eating Disorder Inventory-3 (EDI-3) in Chilean Youth - Lizana-Calderón, Paula; Cruzat-Mandich, Claudia; Díaz-Castrillón, Fernanda; Alvarado, Jesús M.; Compte, Emilio J. (Frontiers in Psychology, 2022)
The aim was to analyze the psychometric properties of the EDI-3 test to evaluate eating disorders in young Chilean population. Method: The sample consisted of 1091 Chilean adolescents and young people (476 men and 615 women) between 15 and 28 years old, from the Metropolitan Region, and four regions from the coast and south-central zone of the country. The reliability and factorial structure of the instrument were analyzed, replicating the confirmatory factor analyzes of Brookings et al. (2020), evaluating four additional models that included ESEM, bifactor and two-bifactor. Results: majority of the subscales presented alphas and omegas equal to or greater than .70, with the exception of Asceticism (α = .543, ω = .552) and Interpersonal Alienation (α = .684, ω = .695) scales. , which is consistent with the values of the Spanish and Mexican non-clinical samples. The best fit indices were obtained by the ESEM two-bifactor model, with twelve specific factors corresponding to the EDI-3 subscales and two general orthogonal factors (risk subscales and psychological subscales), consistently with the theoretical basis.